Astragalus ramakianus, a new name for the Persian Astragalus turgidus Podlech (Leguminosae) - Venkatachalam, Sampath Kumar; Karthikeyan, Saravanam (Phytotaxa, 2013)
Astragalus Linnaeus (1753: 755) is the largest genus of flowering plants, comprising about 2400 species in the old world and 500 in the new world (Podlech & Zarre 2013). The Old world species are placed under 136 sections by Podlech & Zarre (l. c.) in their revisionary study of this genus. These sections were broadly grouped under 3 categories: annuals (21 sections with 86 species), perennials with simple basifixed hairs (75 sections with 1393 species) and perennials with bifurcate hairs (40 sections with 919 species).